Identifying and Validating Indicators of Ritualism in the Iranian Higher Education System: A Mixed-Methods Study - Seyed Hedayat Davarpanah; Reza Hoveida; Mostafa Bagherian Far (جامعه شناسی کاربردی)
IntroductionThe higher education system in Iran presents a paradox. Despite the rapid expansion of universities and their pervasive presence in Iranian society, evidence indicates that these institutions struggle to forge a meaningful connection with the community and fail to provide scientific and rational solutions to societal challenges. In other words, while universities in Iran are ubiquitous, they often lack substance (Farastkhah, 2020). It appears that Iranian universities have deviated from their core institutional functions, becoming afflicted by anomie and dysfunction. As Merton (1938) suggests, this results in a form of ritualism. In this context, ritualism can be equated with formalism, encompassing the behaviors, functions, and procedures of university institutions and academic actors. This phenomenon has led the higher education system in Iran away from its primary objectives, inhibiting its ability to fulfill its intended role. Consequently, addressing ritualism as a dysfunction within university performance is crucial. Neglecting its indicators in the core functions of the university—teaching, research, and services—can lead to institutions that lack quality and fail to make a significant impact on society, both formally and functionally.  Materials & MethodsThis research was an applied study that employed a sequential exploratory mixed methods (qualitative-quantitative) approach. In the first phase, qualitative data were collected through unstructured interviews with experts, as well as the analysis of speeches and interviews from various media involving critics of higher education in Iran. Using purposive-snowball sampling and the criterion of "theoretical saturation", unstructured interviews were conducted with 17 university professors, experts, and faculty members. Each interview lasted between 25 and 75 minutes. Data analysis was performed concurrently with data collection, employing thematic analysis to interpret the findings. Given the variability in methods used in thematic analysis and the diverse perspectives of the experts, multiple titles and classifications for themes emerged. In this study, thematic analysis followed Attride-Stirling's (2001) framework at 3 levels: basic themes (codes and key points in the text), organizing themes (categories formed by combining and summarizing basic themes), and global themes (higher-level themes that capture the overarching principles of the text). To ensure the reliability of the research data, we employed methods such as repeated study, data comparison, and summarization and categorization of information while preserving the integrity of the original data. In the second phase, to enrich the research findings, 12 speeches or interviews from experts and critics of higher education in Iran were purposefully selected and analyzed using a thematic analysis approach similar to that of the initial interviews.In the second phase (quantitative), the findings from the qualitative section were validated. Using G*Power software with an effect size of 0.079, an alpha coefficient of 0.05, and a statistical power of 0.80, the estimated sample size was determined to be 270 participants. Sampling in this phase was conducted using a convenience sampling method. A link to the researcher-developed questionnaire derived from the qualitative findings was distributed to faculty members across various public and Azad universities. This process continued until the required sample size for the quantitative phase was achieved. The quantitative questionnaire consisted of 18 items measured on a 5-point Likert scale (ranging from "very much" to "very little"), assessing ritualism across 5 areas: education (2 items), research (8 items), evaluation (4 items), higher education development (3 items), and industry relations (1 item). Data analysis for the quantitative phase was performed using Smart-PLS and SPSS 23 software. To establish the validity of the researcher-developed questionnaire, we assessed content, convergent, and discriminant validity. Its reliability was confirmed through 2 indices: Cronbach's alpha coefficient and composite reliability. Discussion of Results & ConclusionThe qualitative phase of the research identified several indicators of ritualism in Iranian higher education, including: quantitativism, certificationism, symbolism, sanctity of ranking systems, emphasis on publication in ISI journals, a focus on the formal aspects of teaching, a preference for product-oriented approaches over process-oriented ones, and predominance of statistics and methods over the fundamental purposes of research. The quantitative results further demonstrated that the model derived from the qualitative phase exhibited a good fit, with all items associated with ritualism indicators in higher education displaying acceptable factor loadings. Consistent with the qualitative findings, the quantitative data indicated that all indicators of ritualism were assessed at a high and undesirable level. These findings suggested that ritualism and a deviation from institutional functions were prevalent in Iranian universities, particularly in the research domain. While some of this situation could be attributed to the universities themselves, a significant portion stemmed from external conditions, to which these institutions were largely subject. This dysfunction had resulted in the proliferation of institutions that were mere caricatures of innovative universities, rather than genuine centers of learning. To improve the current situation, a thorough review of existing procedures and implementation of appropriate policies and actions are essential.Lastly, it is important to recognize that due to the varying levels of funding, structure, and mission among higher education institutions in Iran (see Ameri, 2015), the findings should be interpreted in relation to the Iranian higher education system at a macro level. Caution is warranted when generalizing these results to specific institutions. Future research should explore and compare the levels of ritualism across different universities and higher education institutions in Iran and other countries.